Hubungan Motivasi Kerja, Karakteristik Individu dan Kompensasi terhadap Disiplin Kerja Perawat Rumah Sakit Cikunir Bekasi Tahun 2018 - Dini Rahmawati Permana (Universitas Batanghari Jambi, 2019)
Discipline is a function of operational human resources management the most important because the better the working discipline employees the better performance is achieved. Factor affecting the discipline of work i.e. the motivation of working nurses to increase productivity, the characteristics of the individuals belonging to each nurse, as well as the existence of the application of the compensation is good for the welfare of nurses. This research aims to look at the description of the work discipline Hospitals Cikunir bekasi as well as find out how relationships work, the characteristics of individual motivation and compensation against the discipline of nursing work in a hospital Cikunir Bekasi. This research uses a quantitative approach with methods